Enhancing Smart Grid Resilience : An Educational Approach to Smart Grid Cybersecurity Skill Gap Mitigation - Pirta-Dreimane, Ruta; Romanovs, Andrejs; Bikovska, Jana; Pekša, Janis; Vartiainen, Tero; Valliou, Maria; Kamsamrong, Jirapa; Eltahawy, Bahaa (MDPI, 2024)
Cybersecurity competencies are critical in the smart grid ecosystem, considering its growing complexity and expanding utilization. The smart grid environment integrates different sensors, control systems, and communication networks, thus augmenting the potential attack vectors for cyber criminals. Therefore, interdisciplinary competencies are required from smart grid cybersecurity specialists. In the meantime, there is a lack of competence models that define the required skills, considering smart grid job profiles and the technological landscape. This paper aims to investigate the skill gaps and trends in smart grid cybersecurity and propose an educational approach to mitigate these gaps. The educational approach aims to provide guidance for competence-driven cybersecurity education programs for the design, execution, and evaluation of smart grids.
Keywords: cybersecurity education; cybersecurity skill gaps; educational approach; smart grid cybersecurity; fi=Tietojärjestelmätiede|en=Information Systems|